Corman's Colon and Rectal Surgery. - Corman, Marvin (Wolters Kluwer, 2015)
"Established for over 25 years and now in its 6th Edition, Corman's Colon and Rectal Surgeryhas been thoroughly updated and abundantly illustrated to provide comprehensive coverage of all diseases and conditions affecting the colon, rectum, and anus. Step-by-step instructions on current operative procedures used to treat these disorders are underscored by the authoritative knowledge and expertise of leaders in the field. Three co-editors of international repute have participated in the creation of this updated volume, but the hand of Dr. Corman can be recognized throughout. The biographic sketches have been considerably expanded. This gold standard reference, often referred to as the 'bible' of the specialty, includes thorough reviews of anatomy, physiology, and related medical topics, as well as an extensive section on diagnostic studies, with a focus on the latest imaging modalities. A full-color interior design that includes unique, detailed art depicting the steps in today's operative procedures. Comprehensive coverage of the latest laparoscopic diagnostic and surgical management techniques in all areas of the specialty. A companion website that includes the fully searchable text"--Provided by publisher